Intensification of Ethylene Production from Naphtha via a Redox Oxy-Cracking Scheme: Process Simulations and Analysis. (October 2018) - Haribal, Vasudev Pralhad; Chen, Yun; Neal, Luke; Li, Fanxing
Abstract: Ethylene production by the thermal cracking of naphtha is an energy-intensive process (up to 40 GJ heat per tonne ethylene), leading to significant formation of coke and nitrogen oxide (NO x ), along with 1.8–2 kg of carbon dioxide (CO2 ) emission per kilogram of ethylene produced. We propose an alternative process for the redox oxy-cracking (ROC) of naphtha. In this two-step process, hydrogen (H2 ) from naphtha cracking is selectively combusted by a redox catalyst with its lattice oxygen first. The redox catalyst is subsequently re-oxidized by air and releases heat, which is used to satisfy the heat requirement for the cracking reactions. This intensified process reduces parasitic energy consumption and CO2 and NO x emissions. Moreover, the formation of ethylene and propylene can be enhanced due to the selective combustion of H2 . In this study, the ROC process is simulated with ASPEN Plus® based on experimental data from recently developed redox catalysts. Compared with traditional naphtha cracking, the ROC process can provide up to 52% reduction in energy consumption and CO2 emissions. The upstream section of the process consumes approximately 67% less energy while producing 28% more ethylene and propylene for every kilogram of naphtha feedstock.